Study of polypropylene (PP) cartridge filter characteristics and development of liquid filtration system test rig - Raihan, Abdul Rashid (2012)
The function of cartridge filter is to separate substance or particle from liquid. Cartridge filter is a media to filtrate substance that flow with liquid. Cartridge filter in this project focus for water filtration system that usually used at houses and small scale industry. Volume flow rate relate with pressure of the water that flow through pipe system. Cartridge filter function as a media that reduced pressure from the water flow and call pressure drop. Sediment sand particles function as particles that flow with the water and will filtrate with cartridge filter. Sediment sand make contact on the surface of cartridge filter depend on the volume flow rate of water. Cartridge will clogged because of sediment sand clog on the surface of cartridge filter when tried to enter the cartridge filter. This situation make filtration system has different pressure on the entrance and the exit of cartridge housing. Different pressure call pressure drop represent the pressure drop of the cartridge. From the pressure drop can relate with volume flow rate and determined life span and maximum condition of the cartridge filter. Maximum clogging condition happen because of pressure of cartridge filter does not increase anymore and cartridge filter has fully clogged with sediment sand.